Higher levels of a cytotoxic protein, vaginolysin, in Lactobacillus-deficient community state types at the vaginal mucosa - Nowak, Rebecca G. (Sex Transm Dis, 2018)
Vaginolysin (VLY), a cytotoxic protein produced by Gardnerella vaginalis, may contribute to bacterial vaginosis (BV). Women with G. vaginalis, low levels of lactobacilli, history of vaginal douching, higher Nugent scores, and higher vaginal pH had increased VLY. Inflammatory markers were not highly expressed with increasing VLY. VLY’s role in BV warrants further evaluation.